# Monday September 30 **Last time:** Let $\lieg$ be finite dimensional and $\lieh$ a maximal toral subalgebra. Then $(\Phi, E)$ is a *root system*, and we obtain a bilinear product \begin{align*} \inner{\wait}{\wait}: E\cross E \to \RR \\ (\alpha, \beta) \mapsto \kappa(t_\alpha, t_\beta) .\end{align*} *Examples:* $\lieg = \liesl(3, \CC)$ and $\lieh = \CC h_1 \oplus \CC h_2$ where > Todo: Insert clip image h1, h2 \begin{align*} \alpha_1: \lieh \to \CC \\ h_1 \mapsto 2 h_2 \mapsto -1 .\end{align*} \begin{align*} \alpha_2: \lieh \to \CC \\ h_1 \mapsto -1 h_2 \mapsto 2 .\end{align*} To find $t_{\alpha_i}$, we need to look at $\kappa\mid_\lieh$. > Todo: Insert phone image Since we only need the trace, this suffice, and we find \begin{align*} \left.\begin{array}{c|cc}{h_{1}} & {h_{2}} \\ {h_{1}} & {12} & {-6} \\ {h_{2}} & {-6} & {12}\end{array}\right] .\end{align*} We then get $t_{\alpha_1} = \frac{h_1}{6}$ and $t_{\alpha_2} = \frac{h_2}{6}$. Moreover \begin{align*} \inner{\alpha_1}{\alpha_1} = \kappa(t_{\alpha_1}, t_{\alpha_1}) = \frac 1 3 \in \QQ \\ \inner{\alpha_1}{\alpha_1} = \frac 1 3 \\ \inner{\alpha_1}{\alpha_2} = - \frac 1 6 \\ \inner{\alpha_1}{\alpha_2\dual} = \frac{2\inner{\alpha_1}{\alpha_2}}{\inner{\alpha_2}{\alpha_2}} = -1 \in \ZZ \inner{\alpha_i}{\alpha_i\dual} = \frac{2\inner{\alpha_i}{\alpha_i}}{\inner{\alpha_i}{\alpha_i}} = 2 \in \ZZ .\end{align*} This leads to a nice fact: the matrix $\inner{\alpha_i}{\alpha_j\dual}$ has $\ZZ$ entries, and this is called the *Cartan matrix*. ## Ch.3: Root Systems ### Axiomatics: Reflections Fix a Euclidean space $E$. *Definition:* A *hyperplane* in $E$ is a subspace of codimension 1. A *reflection* in $E$ is an element $s\in \liegl(E)$ such that $$ \theset{ E^s \coloneqq \theset{x\in E \suchthat sx = s} \text{ is a hyperplane } H \text{ and } s(x) = -x\quad \forall x\in E \suchthat (x, H) = 0 }$$ For nonzero $\alpha\in E$, its reflection is \begin{align*} S_\alpha: E \to E \\ \beta \mapsto \beta - \inner{\beta}{\alpha\dual}\alpha .\end{align*} with respect to $H_\alpha = \theset{x\in E \suchthat \inner{x}{\alpha} = 0}$, where $\alpha\dual = \frac{2\alpha}{\inner{\alpha}{\alpha}}$. **Lemma:** Let $\Phi \subseteq E$ be finite such that $S_\alpha(\Phi) = \Phi$ for all $\alpha \in \Phi$. Suppose that $S \in \liegl(E)$ satisfies 1. $S(\Phi) = \Phi$, 2. $S(h) = h$ for all $h\in H$, and 3. $S(\alpha) = -\alpha$ for some $\alpha \in \Phi$, then $S = S_\alpha$, i.e. this uniquely characterizes $S$ *Proof:* Let $\tau = S \circ S_\alpha$. Then $\tau(\Phi) = \Phi$ and $\tau(\alpha) = \alpha$. This $\tau \actson \RR\alpha$ by 1, and similarly $\tau \actson E/\RR\alpha$ by 1 by picking a representative in $H$. Moreover, all eigenvalues of $\tau$ are 1. So the minimal polynomial of $\tau$ divides $(t-1)^{\dim E}$. We want to show that $\tau \divides (t-1)^N$ for some large $N$, which forces $\tau \divides \gcd((t-1)^{\dim E}, t^N - 1) = 1$. For any $\beta \in \Phi$ and $k > \abs{\Phi}$, not all vectors $\beta, \tau(\beta), \cdots \tau^k(\beta)$. So $\beta = \tau^{k_\beta}(\beta)$ for some $k_\beta$ depending on $\beta$ (noting that $\tau$ is invertible.) Multiplying all of these $k_\beta$s together, we can get some $k_\Phi$ that is larger than $\abs \Phi$, and so $\beta = \tau^{k_\Phi}$ for *all* $\beta \in \Phi$. But then $\tau^{k_\Phi} = 1$ in $\liegl(E)$. ### Root Systems **Definition:** A subset $\Phi$ of $E$ a Euclidean space is called a *root system* iff 1. $\abs \Phi < \infty, 0\not\in\Phi$, and $E = \bigoplus_{\alpha\in\Phi} \RR \alpha$ 2. $\alpha \in \phi \implies \CC \alpha \intersect \Phi = \theset{\pm \alpha}$ 3. $\alpha \in \Phi \implies S_\alpha(\Phi) = \Phi$ 4. $\alpha, \beta \in \Phi \implies \inner{\beta}{\alpha\dual} \in \ZZ$. **Definition:** The *rank* of a root system is the dimension on $E$. **Definition:** The *Weyl Group* of $\Phi$ is defined as $$ W = \generators{S_\alpha \mid \alpha \in \Phi} \subseteq \liegl(E) $$ Note that $W \injects \Sigma_{\abs \Phi}$, a permutation group of size $\abs \Phi$. **Lemma:** If $g \in \liegl(E)$ and $g(\Phi) = \Phi$, then for all $\alpha, \beta \in \Phi$, we have \begin{align*} g s_\alpha g\inv = s_{g(\alpha)}, \\ \inner{\beta}{\alpha\dual} = \inner{g(\beta)}{g(\alpha)\dual},\\ \inner{\beta}{\alpha\dual} = \inner{w(\beta)}{w(\alpha)\dual}\quad \forall w\in W .\end{align*} *Proof:* Check 1-3 in Lemma 9.1. *Proof of 1:* We have \begin{align*} g s_\alpha g\inv(g(\beta)) = g s_\alpha (\beta) \in g(\Phi) = \Phi \quad \forall \beta \in \Phi, \\ .\end{align*} *Proof of 2:* We have \begin{align*} \theset{g(\beta) \suchthat \beta \in \Phi} = \Phi \implies g s_\alpha g\inv (\Phi) = \Phi \quad \forall h\in gH_\alpha \\ .\end{align*} and so $gs_\alpha g\inv(h) = gg\inv(h) = h$, so $h$ is a fixed point of this map. *Proof of 3:* We have $gs_\alpha g\inv(g(\alpha) = gs_\alpha(\alpha) = -g(\alpha)$, and so $gs_\alpha g\inv = s_{g(\alpha)})$ by Lemma 9.1. Finally, we have \begin{align*} g s_\alpha g\inv (g(\beta)) = g(s_\alpha(\beta)) = g(\beta - \inner{\beta}{\alpha\dual}\alpha) = g(\beta) - \inner{\beta}{\alpha\dual}g(\alpha) \\ = \\ s_{g(\alpha)} = g(\beta) - \inner{g(\beta)}{g(\alpha)\dual}g(\alpha) .\end{align*}